SIGNIFICANCE OF VITAMIN B12 DEFICIENCY IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - DR. SUJATHA RANI AKURI M.D, (International Journal of Pharma and Bio Sciences, 2014)
Nutritional deficiency of B12 is very common in pure vegetarians. Vegetarians suffering from type 2 Diabetes Mellitus and metformin treatment are predisposed to vitamin B12 deficiency and hence diabetic neuropathy and diabetic foot. We estimated B12 levels in patients with type 2 Diabetes Mellitus who are pure vegetarians on metformin therapy (cases), normal healthy individuals (controls). We found that B12 levels are significantly low in type 2 Diabetes Mellitus group when compared to control group with P<0.001 and 95% confidence intervals for mean being 201.65-227.60 and 583.90-802.88 in type 2 Diabetes Mellitus and controls respectively. Hence B12 estimation is necessary to identify B12 deficient patients. From several previous studies, we suggest that parenteral supplementation of vitamin B12 may help to prevent neuropathy, and diabetic foot in type 2 Diabetes Mellitus patients on metformin therapy. Clinical trials are required to establish the mode of supplementation of vitamin B12 for optimum clinical utility.